1996
DOI: 10.1161/01.cir.94.11.2743
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia Confers an Independent Increased Risk of Atherosclerosis in End-Stage Renal Disease and Is Closely Linked to Plasma Folate and Pyridoxine Concentrations

Abstract: A high total plasma homocysteine concentration is an independent risk factor for atherosclerotic complications of end-stage renal disease. Such patients may benefit from higher doses of B vitamins than those currently recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
179
2
9

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(200 citation statements)
references
References 37 publications
10
179
2
9
Order By: Relevance
“…Hyperhomocysteinemia is present in the vast majority of maintenance dialysis patients according to almost all descriptive and prevalent studies (5)(6)(7)(8)(9)(10)(11)(12). In most of such studies, including our current study, Ͼ90% of maintenance dialysis patients have hyperhomocysteinemia, and the mean and median values of tHcy are between 20 and 25 mol/L.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Hyperhomocysteinemia is present in the vast majority of maintenance dialysis patients according to almost all descriptive and prevalent studies (5)(6)(7)(8)(9)(10)(11)(12). In most of such studies, including our current study, Ͼ90% of maintenance dialysis patients have hyperhomocysteinemia, and the mean and median values of tHcy are between 20 and 25 mol/L.…”
Section: Discussionsupporting
confidence: 48%
“…In maintenance hemodialysis (MHD) outpatients, however, the association between tHcy and clinical outcome is inconsistent and even paradoxical. Some studies have shown a poor outcome in MHD patients with hyperhomocysteinemia (5)(6)(7)(8)(9). However, a few recent studies have suggested that a decreased, not an increased, tHcy concentration is related to a higher prevalence of cardiovascular disease and poor outcome in these individuals (10 -12).…”
mentioning
confidence: 99%
“…3,4 Some studies have demonstrated that hyperhomocysteinemia is present in patients with impaired renal function and is associated with CVD. [5][6][7] Only a small number of studies are available on the prevalence and determinants of hyperhomocysteinemia in renal transplant recipients. 8 -15 We undertook this study to 1. estimate the prevalence of hyperhomocysteinemia in renal transplant recipients; 2. examine the relationships between plasma total homocysteine (tHcy) and its metabolic determinants vitamin B 6 , vitamin B 12 , and folic acid; and 3. identify other determinants of tHcy.…”
mentioning
confidence: 99%
“…[16] An increased plasma homocysteine concentration is more among hemodialysis patients, [17,18] and also considered to be risk factor for atherosclerotic complications of ESRD. [19][20][21][22] CKD is associated with increase in triglyceride level, due to increase in VLDL, chylomicrons, and its remnants. Increase in triglycerides is due to delay in catabolism and the increase in triglyceride-rich lipoproteins from liver.…”
Section: Introductionmentioning
confidence: 99%